KONSEP PENGEMBANGAN KAWASAN WISATA PELABUHAN SUNDA KELAPA SEBAGAI PUSAT MUSEUM MARITIM INDONESIA (Universitas Esa Unggul, 2016)
Indonesia is the largest maritime or island nation in the world. Since the maritime era, inter-island shipping and trading have developed by using various types of traditional boats and vessels. Sunda Kelapa Port is one of the historical relics associated with maritime. It was a trade entrance on the island of Java known as a busy pepper port. Foreign ships already docked in this port carrying goods. Sunda Kelapa Harbor now serves as a port of people's voyages and tourist areas. Port as a tourist area has its own attractions for tourists in terms of activities of loading and unloading of goods traditionally and the use of Phinisi Ship. But the port as a tourist area has not been developed properly seen from the existing condition of tourist areas that have not been able to serve the tourists in supporting tourism activities and the utilization of other historical relics. Therefore, it takes a study that aims to assist the development of tourism potential owned by the Tourism Area of Sunda Kelapa Harbor. The research method used in this study is descriptive qualitative method and frequency analysis by extracting information from literature study, interview, questionnaires and field observation. This method is used to determine the condition of the last study area and analyze the factors that hamper the development of the tourist area followed by the formation of the concept in the form of site plan of development of Sunda Kelapa Harbor Tourism Area as the center of Indonesian maritime museum.Â Keywords: concept, port, tourist area, tourism area development, maritime museum